Transition-metal-free, three-component trifluoromethylative heteroarylation of unactivated alkenes: Efficient access to β-trifluoromethylated quinoxalinones and preliminary antifungal evaluation against Magnaporthe grisea. Issue 22 (29th May 2020) - Shao, Zhuoxian; Zhang, Shaoyi; Chen, Yihan; Liu, Yun-Lin; Tang, Ri-Yuan; Li, Zhaodong
Abstract: Herein, a transition-metal-free trifluoromethylative heteroarylation of unactivated alkenes is presented by employing CF3 SO2 Na and quinoxalin-2(1 H )-ones as coupling partners and PhI(OAc)2 as oxidant. This three-component radical domino reaction allows an efficient synthesis of valuable β -trifluoromethyl alkyl quinoxalinones derivatives in a single step in moderate to excellent yields under mild conditions. Mechanistic studies indicated the cascade radical addition pathway controlled by radical polar. This three-component strategy readily affords synthetically and biologically important trifluoromethyl- and quinoxalinones -containing framework, which has been demonstrated by the preliminary antibacterial evaluation against Magnaporthe grisea for the first time. Graphical abstract: Image 1 Highlights: Herein, a transition-metal-free trifluoromethylative heteroarylation of unactivated alkenes is presented by employing CF3 SO2 Na and quinoxalin-2(1 H )-ones as coupling partners and PhI(OAc)2 as oxidant. This three-component radical domino reaction allows an efficient synthesis of valuable β -trifluoromethyl alkyl quinoxalinones derivatives in a single step in moderate to excellent yields under mild conditions. Mechanistic studies indicated the cascade radical addition pathway controlled by radical polar. This three-component strategy readily affords synthetically and biologically important trifluoromethyl- and quinoxalinones -containing framework, which has been demonstrated by the preliminary antibacterial evaluation against Magnaporthe grisea for the first time.